US patent no. 6,950,760 B2: Startup and operational techniques for a digital flowmeter - Henry, M; Zamora, M (United States Patent and Trademark Office, 2005)
Startup and operational techniques for a digital flowmeter are described. The techniques select an optimal mode of operation for the digital flowmeter, depending on a current environment of the flowmeter. For example, during a startup operation of the flowmeter, the mode of operation might include a random sequence mode, in which filtered, random frequencies are applied as a drive signal to a flowtube associated with the digital flowmeter. Once the flowtube reaches a resonant mode of vibration, the digital flowmeter may transition to a positive feedback mode, in which a sensor signal representing a motion of the flowtube is fed back to the flowtube as a drive signal, as part of a feedback loop. Once an oscillation of the flowtube is achieved and analyzed, a digital synthesis mode of operation may be implemented, in which the analyzed sensor signals are used to synthesize the drive signal. In either the positive feedback mode or the digital synthesis mode, the digital flowmeter may revert to a previous mode to regain stable and desired oscillation of the flowtube, such as might be required during a recovery operation associated with a disturbance to an operation of the digital flowmeter.